Examining the Feasibility of Waqf (Islamic endowment)-based Islamic Insurance Product from the Malaysian Legal Perspective - Megat Laksana, Nan Noorhidayu; Che Mohd Salleh, Marhanum; Che Embi, Nor Azizan (2017)
Compare to other countries, control power over the Islamic endowment fund (Waqf) in Malaysia is basically put under one statutory body for each state called State Islamic Religious Council. The worse scenario is, there is no standard shared among these councils in terms of managing the Waqf fund (asset) where each state council had their own enactment to govern the management of the fund. In this context, this study tries to discuss the feasibility of Waqf (Islamic Endowment)-based Islamic insurance product to be practiced in Malaysia considering the opinion from the state Islamic religious council and legal experts in the industry. Adopting qualitative methodology, focus group discussion with the council representatives and legal experts have been conducted to achieve the research objective. Overall, it is found that all respondents have agreed with the proposed Waqf-based Islamic insurance product as it has special values that may inculcate the culture of brotherhood in society as this concept encourages people to give something to others without receiving any return especially in financial matters. Hence, a part of their agreement, the councils has stated their concern on Waqf enactments which were different among the states in Malaysia and based on discussion with the legal experts, they have proposed to adopt agency principle in order to cater the issue of control over the waqf fund. This study contributes in discussing the feasibility of the Waqf principle (endowment) to be introduced in the Islamic insurance products from the legal perspective.